Pilot Study of F18-Florbetapir in the Early Evaluation of Cardiac Amyloidosis - Sperry, Brett W.; Bock, Ashley; DiFilippo, Frank P.; Donnelly, Joseph P.; Hanna, Mazen; Jaber, Wael A. (Frontiers in Cardiovascular Medicine, 2021)
Background: Cardiac amyloidosis is an increasingly recognized etiology of heart failure, in part due to the rise of non-invasive nuclear bone scintigraphy. Molecular imaging using positron emission tomography (PET) has promised the direct visualization of cardiac amyloid fibrils. We sought to assess the performance of F18-florbetapir PET in patients with a potential for cardiac amyloidosis in order to identify early disease. Methods: We performed a pilot study of 12 patients: one with asymptomatic transthyretin cardiac amyloidosis, seven with a potential for developing cardiac amyloidosis (two smoldering myeloma and five with extracardiac biopsy demonstrating transthyretin amyloid deposits and negative technetium pyrophosphate scans), and four controls. Patients were imaged with PET/CT in listmode 10–20 min after receiving F18-florbetapir. Static images were created from this acquisition, and mean standardized uptake values (SUVs) of the left ventricular myocardium, blood pool, paraspinal muscles, and liver were calculated. Results: All 12 patients demonstrated radiotracer uptake in the myocardium with mean SUV of 2.3 ± 0.4 and blood pool SUV of 0.8 ± 0.1. The patient with cardiac amyloidosis had SUV of 3.3, while mean SUV for patients at risk was 2.3 ± 0.4 and for controls was 2.2 ± 0.3. After 3 years of follow-up, one patient with SUV below the mean was subsequently diagnosed with ATTR cardiac amyloidosis. Conclusion: In this cohort, PET with F18-florbetapir demonstrated non-specific radiotracer uptake in the myocardium in all patients using a static image protocol; though, the highest values were noted in a patient with ATTR cardiac amyloidosis. There was no difference in the intensity of F18-florbetapir uptake in at-risk patients and controls. Future studies should continue to investigate metabolic PET tracers and protocols in cardiac amyloidosis, including in early disease.